Caring deception : community art in the suburbs of Aotearoa (New Zealand) : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Fine Arts at Massey University, Wellington, New Zealand - Barlow, Tim (Massey University, 2016)
In Aotearoa (New Zealand), community art practice has a disadvantaged status and a poorly documented national history. This thesis reinvigorates the theory and practice of community art and cultural democracy using adaptable and context-specific analyses of the ways that aesthetics and ethics can usefully co-exist in practices of social change. The community art projects in this thesis were based in four suburbs lying on the economic and spatial fringes of Aotearoa. Over 4 years, I generated a comparative and iterative methodology challenging major binaries of the field, including: ameliorative vs. disruptive; coloniser vs. colonised; instrumental vs. instrumentalised; and long term vs. short term. This thesis asserts that these binaries create a series of impasses that drive the practice towards two new artistic categories, which I define as caring deception and the facade. All the projects I undertook were situated in contested space, where artists working with communities overlapped with local and national governments aiming for CBD and suburban re-vitalisation, creative city style initiatives, community development, grassroots creative projects, and curated public-art festivals. I worked within and around these structures, by practicing a methodology of caring deception. I applied a selection of artistic terms of engagement to vernacular structures such as public fountains, festival marquees, popup venues and community centres to negotiate deceit, resentment and care in the making of the art work. This thesis asserts that the methodology of caring deception creates a social ethics in action that can become embodied in the form of the art work.
Keywords: Tim Barlow; Criticism and interpretation; Community art projects; Artists and community; Social ethics; New Zealand